2017
DOI: 10.1155/2017/1806069
|View full text |Cite
|
Sign up to set email alerts
|

Detection of MicroRNA in Hepatic Cirrhosis and Hepatocellular Carcinoma in Hepatitis C Genotype-4 in Egyptian Patients

Abstract: Background In Egypt, the prevalence of chronic hepatitis C (CHC) infection is 13.8% of whole population and about 80% of the patients with hepatocellular carcinoma have underling hepatitis C. Aim This study was designed to assess the diagnostic value of plasma miR-122 and miR-21 in patients with CHC, genotype-4, to detect fibrosis progression versus noninvasive indices and their diagnostic value in detection of early stages of hepatocellular carcinoma (HCC). Methodology A prospective study that included 180 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 43 publications
4
26
0
Order By: Relevance
“…This is may be happened by genotypes. Demerdash et al, (2017) reported that about 90% of Egyptian patients suffering from HCV belong to genotype-4 and this differs from other countries at which HCC patients suffering from other genotypes.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…This is may be happened by genotypes. Demerdash et al, (2017) reported that about 90% of Egyptian patients suffering from HCV belong to genotype-4 and this differs from other countries at which HCC patients suffering from other genotypes.…”
Section: Discussionmentioning
confidence: 82%
“…The HCC incidence is rising all through the world because of a rising incidence of HBV and HCV infection, due to an increase in prevalence of non-alcoholic fatty liver disorder (Njei et al, 2015). In Egypt, HCC is the fourth common cancer and is the second reason of most cancers mortality in both sexes (Demerdash et al, 2017). The burden of HCC increased with a doubling within the occurrence rate in the past 10 years and this was attributed to excessive occurrence of HCV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxia-induced vascular endothelial growth factors (VEGF) and their counteracting soluble receptors (sVEGFRs) are major pathophysiological players. Their inducibility is orchestrated by the transcription regulator, the hypoxia-inducible factor-1α (HIF-1α) [17][18][19][20]. HCV infections promote oxidative stress, while downregulating VEGF mRNA expression very early after infection that rebounds in the long term [9].…”
Section: Introductionmentioning
confidence: 99%
“…The marked variability in VEGF and sVEGFR concentrations in HCV-induced hepatic disease makes them weak indicators for the progression of chronic liver disease in cirrhotic patients. However, they may reflect the increases in portal hypertension and/or the decreases in hepatic regenerative activity [18][19][20][21]. Moreover, the interaction between the virus and the immune system response is a critical pathogenic mechanism.…”
Section: Introductionmentioning
confidence: 99%